Agricultural extension in Central Asia: existing strategies and future needs - Kazbekov, Jusipbek S.; Qureshi, Asad Sarwar (International Water Management Institute, 2011)
Agriculture is at the forefront of the development objectives of the republics of Central Asia (CA). Since independence in 1991, these countries have undergone transitions from being centrally planned economies to market-oriented systems, which did not include the creation of agricultural extension systems. This paper provides information on the current status of the agricultural extension systems in CA with special reference to Kyrgyzstan, Tajikistan and Uzbekistan. We reviewed the existing extension strategies, donor- and state-driven initiatives to revitalize the agricultural extension systems, informal linkages that nongovernmental organizations play in helping a limited number of farmers, and provided recommendations on ways to further improve the agricultural extension services in CA. The information related to each country was analyzed separately. This is because, after independence, each republic in CA had initiated their agricultural reforms with specific objectives and has now established their unique agricultural systems that differ contextually. However, due to having the same history and agricultural system that existed during the Soviet times, we tried to give a historical perspective to the unified agricultural extension system that existed before independence.